Prehospital rapid sequence induction by emergency physicians: Is it safe?. Issue 1 (1st January 2001) - Mackay, C A; Terris, J; Coats, T J
Abstract : Objectives —To determine if there were differences in practice or intubation mishap rate between anaesthetists and accident and emergency physicians performing rapid sequence induction of anaesthesia (RSI) in the prehospital setting. Methods —All patients who underwent RSI by a Helicopter Emergency Medical Service (HEMS) doctor from 1 May 1997 to 30 April 1999 were studied by retrospective analysis of in-flight run sheets. Intubation mishaps were classified as repeat attempts at intubation, repeat drug administration and failed intubation. Results —RSI was performed on 359 patients by 10 anaesthetists (202 patients) and nine emergency physicians (157 patients). Emergency physicians recorded a larger number of patients as having Cormack and Lehane grade 3 or 4 laryngoscopy than anaesthetists (p<0.0001) but were less likely to use a gum elastic bougie to assist intubation (p=0.024). Patients treated by emergency physicians did not have a significantly different pulse, blood pressure, oxygen saturation or end tidal CO2 to patients treated by anaesthetists at any time after intubation. Emergency physicians were more likely to anaesthetise patients with a Glasgow Coma Score >12 than anaesthetists (p=0.003). There were two failed intubations (1%) in the anaesthetist group and four (2.5%) in the emergency physician group. Repeat attempts at intubation and repeat drug administration occurred in <2% of each group. Conclusions —RSI performed by emergency physicians was not associated with a significantly higher failure rate or an increased number of intubation mishaps than RSI performed by anaesthetists. Emergency physicians were able to safely administer sedative and neuromuscular blocking drugs in the prehospital situation. It is suggested that emergency physicians can safely perform rapid sequence induction of anaesthesia and intubation.